2019
DOI: 10.23869/bphjbr.24.1.20194
|View full text |Cite
|
Sign up to set email alerts
|

In silico exploration the phenolic compound of olive leaves as acetylcholinesterase enzyme (AChE) inhibitor for Alzheimer’s disease therapy

Abstract: Olive (Olea europaea) have been cultivated and grown well in tropical climates such as Indonesia. Indonesia local community have used olive as herbal medicines due to its active compounds known as oleuropein that has many biological activities including as neurotherapy in Alzheimer's disease. The purpose of this study is to explore the potential phenolic compounds of olive and examine the acetylcholinesterase (AChE) inhibitory activity displayed by different olive polyphenols through a silico approach. The bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Several in vivo studies have shown that OL is one of the most actively investigated biophenols that are potent amyloid inhibitors (Casamenti et al., 2015; Cordero et al., 2018). The major mechanism behind this action of OL is that it inhibits the formation of Aβ toxic aggregates and also causes a marked reduction in neuroinflammation and ROS/RNS production by mitochondria (Mubarakati et al., 2019; Omar et al., 2019). OLA has been found to interfere with the formulation of Aβ aggregates (Rigacci et al., 2011), amylin (Rigacci et al., 2010), and Tau (Daccache et al., 2011).…”
Section: Neuroprotective Role Of Oleuropeinmentioning
confidence: 99%
“…Several in vivo studies have shown that OL is one of the most actively investigated biophenols that are potent amyloid inhibitors (Casamenti et al., 2015; Cordero et al., 2018). The major mechanism behind this action of OL is that it inhibits the formation of Aβ toxic aggregates and also causes a marked reduction in neuroinflammation and ROS/RNS production by mitochondria (Mubarakati et al., 2019; Omar et al., 2019). OLA has been found to interfere with the formulation of Aβ aggregates (Rigacci et al., 2011), amylin (Rigacci et al., 2010), and Tau (Daccache et al., 2011).…”
Section: Neuroprotective Role Of Oleuropeinmentioning
confidence: 99%
“…This structural difference may contribute to the higher affinity of myricetin towards BChE. Molecular docking (MD) is a key technique in structural molecular biology, as confirmed by numerous literature reports [96][97][98][99][100]. MD was used to observe and confirm possible interactions between MYR and AChE/BChE, which are important targets for neuroprotection.…”
Section: Resultsmentioning
confidence: 99%
“…Simple phenolic acids, such as gallic acid, also inhibit platelet aggregation and activation via the inhibition of the phosphorylation of PKCα/p38 MAPK and Akt/GSK3β (Oh et al, 2012). Besides, Mubarakati et al, (2019) showed that based on molecular docking analysis, phenolic compounds such as dimethyl-oleuropein in olives have acetylcholinesterase (AChE) inhibitory activity for the treatment of Alzheimer's disease. CMUJ.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the application of the methods of virtual screening is limited to the structures of the compounds that can be counted and to compounds known to have ties with other compounds. There are a lot of studies doing computer screening and active compound molecular docking to a target protein (Kumar, et al, 2017;Mubarakati, et al, 2019;Sarkar, et al, 2021). Nevertheless, these predictive results require validation through in vitro and in vivo toxicological and pharmacological assays and experimental bioavailability tests for this main compound concerning hypertension prevention.…”
Section: Discussionmentioning
confidence: 99%